Retrieving the Aphrodite of Hermogenes of Cythera - Corso, Antonio (Hyperboreus, 2015)
In this article, the statue of Aphrodite by Hermogenes of Cythera is discussed. This statue is recorded by Pausanias, and was located in the temple of the love goddess in the forum of the Roman colony of Corinth. The temple is Augustan, thus probably the statue and its artist are also of this period. It is likely that this Aphrodite was represented on Roman imperial coins: a naked standing female wreathing herself with her right hand and looking at a mirror held in her left hand. A statuette from Corinth may also be a copy of this work. A bronze Aphrodite of the same style had been set up in Corinth already in the 4th century BC (as it is known thanks to a statuette of Corinthian production from Thera), but this bronze statue had been brought to Rome by Mummius. The new work by Hermogenes was meant to replace it.